Gamifying Structural Analysis Assessments for First Year Architecture Engineering Students - Amany Georgy Botros Micheal (International Journal of Engineering Education, 2021)
Structural analysis modules delivered to first year in Architecture Engineering students is a real challenge for both teacher and students. Usually the assignments adopted in such modules are on campus  exams.  Such strategy may assess the capacity of the students to employ different sets of equations to solve a problem. However, this is not enough for a vivid education atmosphere. Transforming the assessments to digital simulations is the best solution for the education process. Digitalization is more appealing to nowadays students and it gives the teacher a wide spectrum of discussions without the hindrance of calculations time. The obstacle is that students at the first semester in engineering schools are not capable of dealing with solution packages. This paper presents a digital simulation of different structures using a simple tool based on closed-form equations. The tool is employed to generate different assessments that enable students to grasp the interaction between geometry, loading, boundary conditions, and internal forces and visualize the mutual effect. This cannot be achieved using classical assessments as it requires much calculation time. Furthermore, transforming this tool into an offline mobile app helps to gamify this tough module. This tool enables the students to work remotely in groups taking into account the Covid -19 pandemic social distancing. The students can submit a report where they demonstrate their understanding and conclusions.